Characterization of Hydroxyapatite Derived from Scallop Shell Waste Synthesized by Sonochemical Method with Different Temperature Calcination - Pramono, Diki Dwi; Puspitasari, Poppy; Aminnudin, Aminnudin; Razak, Jeefferie Abd (Universitas Negeri Malang, 2024)
One common bio-ceramic material used in the biomedical industry is hydroxyapatite. Because of its crystallographic and molecular resemblance to the hard tissues of the human body, hydroxyapatite is thought to form. Scallop shells are one natural source of hydroxyapatite, which is high in calcium. This study examines how the calcination temperature affects the characteristics of hydroxyapatite made from leftover scallop shell. Hydroxyapatite was synthesized via the sonochemical method, with calcination conducted at temperatures of 900°C, 1000°C, and 1100°C. The hydroxyapatite that was prepared was assessed using X-ray diffraction (XRD) to determine the phase and crystallite size, Scanning Electron Microscopy (SEM) to conduct a morphological investigation, and Fourier Transform Infrared (FTIR) spectroscopy to conduct a functional group analysis. Phases resulting from varying calcination temperatures include hydroxyapatite and β-tricalcium phosphate. The crystallite size of hydroxyapatite enhanced with rising temperature. The morphology of hydroxyapatite exhibited agglomeration in all samples, with grain size escalating alongside the increase in calcination temperature. The functional groups generated under the three temperature fluctuations include O-H, P-O, PO43-, and O–P–O groups. The calcination temperature significantly influences the characteristics of produced hydroxyapatite and impacts its biocompatibility as a bone implant material.